Stoichiometrically controlled C–(A)–S–H/N–A–S–H gel blends via alkali-activation of synthetic precursors. (4th August 2015) - Walkley, B.; Provis, J. L.; San Nicolas, R.; Sani, M.-A.; van Deventer, J. S. J.
Abstract : The extent to which the composition of the reaction mix affects the formation of a biphasic C–(A)–S–H/N–A–S–H geopolymer framework, and how the interaction of these phases affects geopolymer microstructure, can only be studied by strict stoichiometric control. Stoichiometrically controlled geopolymers containing both C–(A)–S–H and N–A–S–H gels are produced here by reaction of a sodium silicate solution with calcium aluminosilicate powders, which were synthesised via a novel solution-polymerisation method utilising polyethylene glycol as a polymer carrier to sterically inhibit movement of precursor cations. Increased Ca content in the reaction mix appears to promote greater formation of a C–(N)–(A)–S–H gel, while reduced Ca content and increased Al and Si content promote greater formation of an N–A–S–H gel in addition to the main C–(A)–S–H reaction product. The stoichiometrically controlled geopolymers constitute a chemically simplified model system through which the nature of the biphasic C–(A)–S–H/N–A–S–H gels present in alkali activated binders can be studied.